A comparison of the biogenic volatile organic compound emissions from the fine roots of 15 tree species in Japan and Taiwan. Issue 4 (4th July 2018) - Tsuruta, Jun; Okumura, Motonori; Makita, Naoki; Kosugi, Yoshiko; Miyama, Takafumi; Kume, Tomonori; Tohno, Susumu
ABSTRACT: Biogenic volatile organic compounds (BVOCs) play important roles in biosphere‒atmosphere interactions and communications among organisms, although little is known about the characteristics of BVOCs in the pedosphere and particularly emissions from fine roots. We evaluated the effects of cutting the fine roots of two tree species on BVOC emissions during sampling and compared the BVOC and CO2 emission rates in the roots of 15 tree species in forests in Japan and Taiwan. The BVOC emission rate in Pinus densiflora roots increased as the number of cross-sections increased. When the cross-section of a P. densiflora root was outside the sample bag, the BVOC emission rate was not affected by application of a cutting treatment. The mean BVOC emission rates in the fine roots of each of 15 tree species ranged from 0 to 0.38 nmol g −1 s −1 for monoterpenes and 0 to 0.10 nmol g −1 s −1 for a sesquiterpene (longifolene). The monoterpene emission rates in fine roots were very high for some gymnosperm and ectomycorrhizal species ( Pinus densiflora 0.38 ± 0.31 nmol g −1 s −1 and Abies firma 0.19 ± 0.08 nmol g −1 s −1 ). The longifolene emission rates in fine roots were highest for one gymnosperm and arbuscular mycorrhizal species ( Chamaecyparis pisifera 0.10 ± 0.10 nmol g −1 s −1 ). The proportional carbon ratio of BVOCs to CO2 in emissions from fine roots ranged from 0 to 67% among the 15 tree species. Distinct patterns in the exact BVOC compounds and their emission rates indicated species-specific carbon availability in fine roots.